Health, lifestyle habits, and physical fitness among adults with ADHD compared with a random sample of a Swedish general population. Issue 1 (1st January 2018) - Björk, Annette; Rönngren, Ylva; Selander, John; Vinberg, Stig; Hellzen, Ove; Olofsson, Niclas
ABSTRACT: Background : Persons with Attention Deficit Hyperactive Disorder (ADHD) represent a high-risk population according to health and lifestyles. In the present study, 48 adults with ADHD were recruited to a forthcoming lifestyle intervention. The ADHD sample was matched to a random sample of 42 persons from a Swedish general population that was selected from LIV (a Lifestyle-Performance-Health project).Objective : To identify potential differences in health, lifestyle habits, and physical fitness between adults with and without ADHD.Method : Self-reported questionnaires and physical fitness tests.Results : The ADHD group show worse health outcomes with higher odds ratios for bad general health (OR;13 CI; (3, 4–50)), and poorer lifestyle habits with higher odds ratios for low weekly exercise (OR; 3, 8 CI; (1, 2–13)). When adjusting for education, employment status, and cash margin, the ADHD sample did not show decreased aerobic fitness (OR; 0, 9 CI; (0, 8–1, 0), but lower odds ratios for doing less sit-ups (OR; 0, 6 CI; (0, 4–0, 9)) compared to the general population group.Conclusion : It is not possible to prove that the ADHD diagnosis itself cause the worse health and lifestyle. Other lifestyle factors may have negative consequences of adult ADHD, such as lower levels of education, less succeed in working life, and minor financial margins.